Donor deferral rates after the implementation of a new German blood donor questionnaire - Müller-Steinhardt, Michael; Weidmann, Christian; Brade, Joachim; Klüter, Harald (Transfusion medicine and hemotherapy, 2012)
Background: The implementation of a new national German blood donor questionnaire was proposed to improve donor and recipient safety. Methods: We compared deferral/exclusion rates of whole blood donors before (May 2010, n = 64,735) and after (May 2011, n = 71,687) the implementation of a new blood donor questionnaire. Considering seasonal variations, analysis was performed with respect to collection site (mobile vs. fixed), sex, donor status (first-time vs. repeat), age, and the frequencies of sexual risk behavior and other reasons for deferral. Results: We observed a statistically significant increase (p < 0.001) of the overall deferral/exclusion rate from 6.2 to 8.1%, irrespective of type of collection site (fixed: from 6.0 to 8.5%; mobile: from 6.2 to 8.0%), sex (females: from 7.5 to 9.9%; males: from 5.1 to 6.6%), donor status (first-time donors: from 19.7 to 24.7%; repeat donors: from 4.6 to 6.3%) or age (18-29 years: from 9.1 to 11.7%; 60-71 years: from 5.1 to 6.6%). Confidential self-exclusion increased from 0.08 to 0.14% (p < 0.001). Besides risk behavior, various medical reasons could be identified that explain this increase. Conclusions: The new blood donor questionnaire resulted in an increased deferral/exclusion of all donor groups. Thus the impact on future blood supply must be considered carefully, and long-term studies and investigation of donor acceptance will be needed.
Published online: December 23, 2011
Gesehen am 21.08.2018